Investigation of a Medieval Pilgrim Burial Excavated from the Leprosarium of St Mary Magdalen Winchester, UK. - Simon Roffey; Katie Tucker; Kori Filipek-Ogden; Janet Montgomery; Jamie Cameron; Tamsin O'Connell; Jane Evans; Phil Marter; G Michael Taylor (Public Library of Science (PLoS), 2017)
We have examined the remains of a Pilgrim burial from St Mary Magdalen, Winchester. The individual was a young adult male, aged around 18-25 years at the time of death. Radiocarbon dating showed the remains dated to the late 11th-early 12th centuries, a time when pilgrimages were at their height in Europe. Several lines of evidence in connection with the burial suggested this was an individual of some means and prestige. Although buried within the leprosarium cemetery, the skeleton showed only minimal skeletal evidence for leprosy, which was confined to the bones of the feet and legs. Nonetheless, molecular testing of several skeletal elements, including uninvolved bones all showed robust evidence of DNA from Mycobacterium leprae, consistent with the lepromatous or multibacillary form of the disease. We infer that in life, this individual almost certainly suffered with multiple soft tissue lesions. Genotyping of the M.leprae strain showed this belonged to the 2F lineage, today associated with cases from South-Central and Western Asia. During osteological examination it was noted that the cranium and facial features displayed atypical morphology for northern European populations. Subsequently, geochemical isotopic analyses carried out on tooth enamel indicated that this individual was indeed not local to the Winchester region, although it was not possible to be more specific about their geographic origin.